In silico structural and functional annotation of nine essential hypothetical proteins from Streptococcus pneumoniae - Razali, Khairiah; Abdul Hamid, Azzmer Azzar; Md Zin, Noor Hasniza; Mohammad Bunnori, Noraslinda; Ahmad Yusof @Hanafi, Hanani; Kamarudin, Kamarul Rahim; Mohammed Rehan, Aisyah (Chemistry Department, Universitas Gadjah Mada, Indonesia, 2019)
The ability of Streptococcus pneumoniae to induce infections relies on its virulence factor machinery. A previous CRISPR interference (CRISPRi) study had identified 254 essential proteins that may be responsible for the pathogenicity of S. pneumoniae serotype 2 strain D39. However, 39 of them were functionally and structurally uncharacterized. Hence, by using in silico approach, this study aimed to annotate the function and structure of these un-annotated proteins. Initially, all 39 proteins went through primary screening for template availability and pathogenicity. From there, 11 of them were selected and underwent further physicochemical, functional, and structural categorization through an integrated bioinformatics approach by means of amino acid sequence- and structure- based analyses. The obtained data revealed that 9 targeted proteins showed a high possibility to be involved in either cell viability or cell pathogenicity mechanism of the bacterium, with SPD_1333 and SPD_1743 being the two most promising proteins to be further studied. Findings from this study can help in facilitating a better understanding of pathogenic ability of this microorganism and enhance drug development and target identification processes in the aim of improving pneumococcal disease control.